Sámi media and indigenous agency in the Arctic north - Cocq, Coppélie; DuBois, Thomas A. (Thomas Andrew), 1960- (New directions in Scandinavian studies., 2020)
"Digital media, GIFs, films, TED Talks, tweets and more, have become an integral part of daily life and, unsurprisingly, Indigenous people's strategies for addressing the historical and ongoing effects of colonization. Thomas DuBois and Coppélie Cocq consider how Sámi (formerly called Lapp) people of Norway, Finland and Sweden have become expert at using digital media for personal and communal activism. Grounding their analysis in the 'creative image making' Sámi songwriters and poets employed in the 1970s A'ltta' dam protests, the authors examine contemporary efforts, from a singer creating YouTube music videos that combine rock music and joik (a traditional Sámi musical genre) to anonymous activist groups sharing images of James Bond in Sámi ga'kti (Sámi traditional dress) via Facebook. They demonstrate how these artists and activists stitch together Indigenous and global symbols to create decolonizing works that invite Sámi across Scandinavia into greater engagement with their natal culture while simultaneously convincing a global non-Sámi audience of Sámi resilience, continuity and inherent right to self-determination"--